(untitled) (Palíndromo, 2014)
This article aims to provide support for a reading in the classroom ready made Fontaine Marcel Duchamp and Soft Toilet of Claes Oldenburg. These works were analyzed using assumptions of Greimas Semiotics, making use of the theories of Ana Claudia de Oliveira and analyzes made by the critic and historian Rosalind E. Krauss. This reading provides methods of description that allows a broad view of the work, with the aim of bringing the viewer to enjoy it aesthetically. At the end of the analysis, we found that the two sculptures, even having the common theme, have their differences, as Duchamp appropriates objects and ready Oldenburg subverts the function of the object, presenting to the public forms softened.